Human Capital Accounting: Global Theoretical Model - San Lio (Asian Journal of Finance & Accounting, 2024)
Human Capital (HC) is the sole intervening factor for a competitive hedge in all firms: merchandising, manufacturing, or servicing. However, the need for HC is enhanced in service firms because only they can act. All requisite tangible and intangible assets of firms are accounted for as material investments in their financial reports for improved decisions by managers and other stakeholders. However, contemporary organizations are unable to account for their HC investments because there is no Generally Accepted Legal Framework (GALF). This is even though HC accounting discipline has attracted attention in most jurisdictions, although it was largely disregarded in some parts of the world and the deliberations date back to the early sixties of the last century. Could the exploration of HC accounting underpinning theories offer practitioners research insights?